Social Work Challenges in the XXI Century: Perspectives from the USA - López Peláez, Antonio (Colección de libros electrónicos de ULoyola, 2015)
By the work challenge we refer to conditions or situations that demand new and innovative responses and to situations that may demand time, knowledge and/or resources we may not currently have. Examples of challenges faced by our profession of social work may include: the incorporation of new technologies in our professional practice, the persistence of social exclusion, or the need to provide effective and culturally sensitive interventions rural as well as urban environments. This book discusses new technologies as they relate to our profession, leadership, research and professional practice, empowerment and community organizations, rural social work, history and characteristics of social work in Alaska, specific problems of the Latino elderly, corporal punishment in education, Trauma-Informed Service Delivery Systems and Child Welfare Services. The various chapters provide insight into the practical issues faced by social workers in the United States even though the issues addressed do not by any means represent an exhaustive or comprehensive list.